Mitigation strategies for heat-related illness during mass gatherings: Hajj experience - Almuzaini, Yasir; Alburayh, Marriyah; Alahmari, Ahmed; Alamri, Fahad; Sabbagh, Abdulrahman Y.; Alsalamah, Majid; Khan, Anas (Frontiers in Public Health, 2022)
Introduction To mitigate morbidity, mortality, and impacts of heat-related illnesses (HRIs) on health, it was vital to implement a comprehensive framework for HRI prevention and control. A recognized tool from the field of trauma prevention known as the Haddon matrix was applied. The matrix states that any event is affected by three factors: host, agent, and environment. In addition, another recognized tool known as the combined model was used in this study. The combined model is a three-dimensional model that includes the idea for the three axes of Haddon's matrix with the methodology of the community risk reduction (CRR) model. Aim of the study To identify the environmental and individual risk factors of HRIs based on the Haddon matrix and the recommended prevention strategies by the CRR tool by using the combined model. Methodology An extensive literature review was conducted to assess all the risk factors associated with HRI, as well as preventive measures. Then the Haddon matrix was used to structure, separating human factors from technical and environmental details and timing. After that, the combined model was used to set all responses and mitigation measures for each element obtained from the Haddon matrix tool. Conclusion Projected increases in heat stress over the globe require the formulation and implementation of evidence-based HRI mitigation and preventive measures. In this study, we implemented the combined model that was utilized as a systematic strategy for the more theoretical framework of Haddon's matrix. Using the Haddon matrix to determine the HRI risk factors and the combined model to mitigate its impact was practical and helpful in planning, preparedness, and mitigating the HRIs during Hajj, provided a broad approach equivalent to the Swiss cheese model, and would facilitate an informed decision.